Bosnia and Herzegovina 20 years on from Dayton - Mayne, A (Refugee Studies Centre, University of Oxford, 2015)
The coming two-and-a-half years represent what is possibly the last window of opportunity to accomplish what the Dayton Peace Agreement’s Annex 7 set out to achieve